The Potential of a Multidecade Spaceborne Lidar Record to Constrain Cloud Feedback. Issue 10 (23rd May 2018) - Chepfer, H.; Noel, V.; Chiriaco, M.; Wielicki, B.; Winker, D.; Loeb, N.; Wood, R.
Abstract: Synthetic multidecadal spaceborne lidar records are used to examine when a cloud response to anthropogenic forcing would be detectable from spaceborne lidar observations. The synthetic records are generated using long‐term cloud changes predicted by two Coupled Model Intercomparison Program 5 models seen through the COSP/lidar (CFMIP, Cloud Feedback Model Intercomparison Project, Observation Simulators Package) and cloud interannual variability observed by the CALIPSO (Cloud Aerosol Lidar and Infrared Pathfinder Satellite Observations) spaceborne lidar during the past decade. CALIPSO observations do not show any significant trend yet. Our analysis of the synthetic time series suggests that the tropical cloud longwave feedback and the Southern Ocean cloud shortwave feedback might be constrained with 70% confidence with, respectively, a 20‐year and 29‐year uninterrupted lidar‐in‐space record. A 27‐year record might be needed to separate the two different model predictions in the tropical subsidence clouds. Assuming that combining the CALIPSO and Earth‐CARE (Earth Clouds, Aerosols and Radiation Explorer) missions will lead to a spaceborne lidar record of at least 16 years, we examine the impact of gaps and calibration offsets between successive missions. A 2‐year gap between Earth‐CARE and the following spaceborne lidar would have no significant impact on the capability to constrain the cloud feedback if all the space lidars were perfectly intercalibrated. Any intercalibration shift between successive lidar missions would delay the capability to constrain the cloud feedback mechanisms, larger shifts leading to longer delays. Plain Language Summary: The atmospheric water cycle has many components (clouds, aerosol, precipitation, and water vapor), and how they interact with the other climate elements to produce the precipitation necessary for life on land is complex. How this cycle will evolve over the coming decades in a warming world is uncertain and must be more fully understood. There are currently unprecedented opportunities to increase our understanding and capacity to predict cloud changes. Pioneering satellite missions developed over the last decade have provided for the first time observed detailed profiles of clouds on a global scale. Such profiles are especially important because they are expected to change faster and with larger amplitudes in response to human‐caused climate modifications than the other characteristics of clouds. Here we show that multidecade global‐scale climate record of cloud profiles obtained by combining observations collected by successive space lidars (pulsed lasers) could likely be used to identify fingerprints of human‐caused cloud modifications. Key Points: Space born lidar record could constrain cloud feedback Intercalibration shift between successive lidar missions would delay the capability to constrain cloud feedback Signatures of longwave cloud tropical cloud feedback might be observed first